Pembinaan Guru Madrasah dalam Penggunaan Integrasi AI (Artificial Intelligence) Sebagai Pengembangan Media Pembelajaran Pendidikan Islam - Mohamad Sodik; Laily Nur Syayidah; Muhammad Khozin Natul Asror (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Abstrak The issue facing madrasah teachers at the Riyadhus Samawi Lodoyo Islamic Boarding School in Blitar is low digital literacy and skills in utilizing Artificial Intelligence (AI) technology as a learning medium. Teachers still rely on conventional methods, requiring coaching to improve their ability to integrate AI. The focus of the community service program is directed at improving teachers' competency in understanding, operating, and utilizing AI applications to produce creative, interactive, and relevant Islamic education learning media. The goal of this community service is to improve madrasah teachers' understanding and skills in using AI technology to develop Islamic education learning media. Furthermore, this activity aims to build teacher confidence in implementing digital technology and encourage the development of a culture of innovative learning within the Islamic boarding school environment. The activities were carried out in several stages, namely: (1) analysis of teacher needs related to the use of technology; (2) basic training on the concepts and ethics of using AI; (3) workshops on creating AI-based learning media such as presentation design, digital modules, and educational videos; and (4) ongoing mentoring for the application of AI in learning. The approaches used were capacity building, training workshops, and practice-based mentoring. Participatory Action Research (PAR) was chosen because it emphasizes collaboration between the community service team and the teacher community at every stage of the activity. PAR allows for collaborative problem identification, action planning, implementation, and evaluation, resulting in more relevant and applicable results. The community service activities demonstrated that teachers experienced significant improvements in their digital competencies. Teachers were able to use various AI applications to create more engaging and interactive Islamic learning media. The resulting learning products were more varied, including learning videos, digital modules, and AI-based presentation materials. Furthermore, these activities increased teachers' motivation to continue innovating and built a technology-based learning ecosystem within the Riyadhus Samawi Lodoyo–Blitar Islamic Boarding School.